Electronic Traffic Law Enforcement in Indonesia - Aras Genda, Erwin; ., Abdul Hakim; Noor, Irwan; Setyowati, Endah (KnE Social Sciences, 2023)
This study aimed to analyze the implementation of Electronic Traffic Law Enforcement (E-TLE) in the South Sulawesi Regional Police area, Indonesia. The research method used is descriptive with a qualitative approach. Data were collected through interviews with the police, document analysis, and field observations. The results showed that the implementation of E-TLE was quite effective for ticketing traffic violators. The process of sending confirmation letters and paying fines was done quickly. Information transparency is also guaranteed through the application. However, there were still obstacles regarding the availability of Internet network infrastructure and the public’s understanding of the E-TLE system. Therefore, it is recommended to increase socialization and infrastructure that support the implementation of E-TLE. Keywords: E-TLE System, Law Enforcement, Traffic Law